(untitled) (Westport, Conn., 1978)
This bibliography is a comprehensive but not exhaustive reference guide for both researchers and those who want specific information on a subject that has been widely explored only in the last two decades.
Keywords: Đông Á,East Asia; Điều kiện kinh tế,Economic conditions